Security based on network topology against the wiretapping attack. - Jain, K. (IEEE Wireless communications)
In wireless networks, an attacker can tune a receiver and tap the communication between two nodes. Whether or not some meaningful information is obtained by tapping a wireless connection depends the security protocols used. One may use cryptographic techniques to secure the communications. In this article we discuss an alternate way of securing the communication between two nodes. We provide a simple security protocol against a wiretapping attack based on the network topology. Although we study the problem from a theoretical perspective, our protocol is easily implementable. Our protocol is at least as secure as any other protocol against these attacks. We show that an attacker can get any meaningful information only by wiretapping those links that are necessary for the communication between the sender and the receiver. We use techniques from network encoding. Our protocol works for any network topology, including cycle networks. We note here that acyclicity is the main assumption in much of the network encoding literature.